Perbedaan Pengaruh Latihan Squat dan Lunges dengan Metode Set terhadap Tinggi Lompatan Pemain Bolavoli - Abdul Jadid; Tono Haryono; Unun Umaran (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to analyze the differences in the effects of squat and lunge exercises performed using the set method on improvements in vertical jump performance among male volleyball players. The research employed a quasi-experimental pretest–posttest two-group design involving 20 participants aged 12–15 years, who were divided into a squat group and a lunge group. The training program was conducted for 7 weeks with a frequency of three sessions per week, and vertical jump height was measured using the Sargent Jump Test. Data were analyzed using paired t-tests and independent t-tests with the aid of SPSS software at a significance level of α = 0.05. The results indicated significant improvements in both groups, with the squat group showing an increase of 3.15 cm (Sig. = 0.000) and the lunge group an increase of 3.65 cm (Sig. = 0.000). However, no statistically significant difference was found between groups (Sig. = 0.237), although descriptively the lunge group demonstrated greater mean improvement (3.65 cm vs. 3.15 cm). In conclusion, both exercises were effective in enhancing vertical jump performance through neuromuscular adaptations, with lunges showing a descriptive advantage due to their unilateral nature that supports functional balance. It is recommended that both exercises be combined in volleyball training programs.